PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT BHAKTI IDOLA TAMA BANDUNG - Tata Maulidin; Nouvandry Alexander; Rita Zulbetti (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aimed to determine the influance of service quality to customer satisfaction at PT Bhakti Idola Tama Bandung. The research method used quantitative research. The data collection technique used observation, interviews with questionnaires and literature studies which had relation to the subject. The data analysis technique used descriptive analysis and inferential analysis (validation test and realibility). Hypothesis test used correlation of rank Spearman, coefficient of determination and significant test of Z. From research conducted, researchers obtained the results that the quality of service to customer satisfaction at PT Bhakti Idol Tama had a positive influence with the results of the Rank Spearman correlation of 0.794 with a significant value of 0,000 ≤ 0, 05 which means the relationship of service quality with customer satisfaction has a strong relationship. The determination test results show 63.04% service quality affects customer satisfaction and the remaining 36.96% customer satisfaction influenced by other factors. From significant test of Z, the results of z_hitung were 4, 96 which means z_hitung ≥ z_tabel. Based on the description above, Ho rejected and Ha accepted, the quality of services has a very significant influence on customer satisfaction.